2018
DOI: 10.1016/j.drugalcdep.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use during cannabis cessation: Use patterns and impact on abstinence in a National Drug Abuse Treatment Clinical Trials Network study

Abstract: Background: It is common for cannabis users to also use tobacco. While data suggest that tobacco users have more difficulty achieving cannabis cessation, secondary analyses of clinical trial data sets may provide insight into the moderating variables contributing to this relationship, as well as changes in tobacco use during cannabis treatment. Those were the aims of this secondary analysis. Methods: The parent study was a multi-site trial of N-acetylcysteine for cannabis dependence conducted within the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 54 publications
(69 reference statements)
1
10
0
1
Order By: Relevance
“…Third, cannabis-tobacco co-use rates among cannabis users in the current study did not appear to be as high as national averages suggest, even in the Southeastern US; 42.1% in this study vs. 69-78% nationally . However, the observed rate in the current study more closely approximates the observed rate in a prior multisite clinical trial for CUD (38%; McClure et al, 2018). It may be the case that those who participate in research studies, even via online recruitment sources, are different from those in the general population (i.e., those who complete household surveys; McClure et al, 2017;Susukida, Crum, Stuart, Ebnesajjad, & Mojtabai, 2016), which may have impacted prevalence rates and the characteristics of the current sample of co-users.…”
Section: Limitationssupporting
confidence: 67%
See 1 more Smart Citation
“…Third, cannabis-tobacco co-use rates among cannabis users in the current study did not appear to be as high as national averages suggest, even in the Southeastern US; 42.1% in this study vs. 69-78% nationally . However, the observed rate in the current study more closely approximates the observed rate in a prior multisite clinical trial for CUD (38%; McClure et al, 2018). It may be the case that those who participate in research studies, even via online recruitment sources, are different from those in the general population (i.e., those who complete household surveys; McClure et al, 2017;Susukida, Crum, Stuart, Ebnesajjad, & Mojtabai, 2016), which may have impacted prevalence rates and the characteristics of the current sample of co-users.…”
Section: Limitationssupporting
confidence: 67%
“…Within a recent national cannabis cessation clinical trial, lower rates of tobacco co-use were found in the overall sample (38%; Gray et al, 2017) compared to national averages of co-use (Pacek et al, 2018;, though in that trial (Gray et al, 2017), tobacco co-use rates varied based on study site and geographical location in the US. In the two study sites that fell within the Southeastern region of the US, 50% of cannabis users were also tobacco users, compared to 34% at other sites (McClure et al, 2018). Taken together, the Southeastern region of the US is unique when considering cannabis and tobacco co-use and worthy of focused study.…”
Section: Introductionmentioning
confidence: 93%
“…The average FTND score was 5.4 (SD = 2.4) and the mean age of smoking initiation was 15.1 years (SD = 4.4). The average FTND score translates to a population of moderately dependent smokers, not unlike averages among smoking cessation populations our team and others have reported [ [30] , [31] , [32] ]. The randomized sample did not significantly differ across group assignment on any of the baseline characteristics (all p s > 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…It is possible that associations between depressive symptoms and subsequent cannabis use were stronger because of the reduced lag time between assessments. Lastly, use of alcohol and tobacco was prevalent in this sample (Squeglia et al 2018;McClure et al 2018). More frequent use of tobacco (McClure et al 2018), but not alcohol (Squeglia et al 2018), was associated with greater cannabis use during treatment.…”
Section: Discussionmentioning
confidence: 68%